The Stacks project

86.8 In case the base ring is a G-ring

If the base ring $A$ is a Noetherian G-ring, then some of the material above simplifies somewhat and we obtain some additional results.

Proof of Lemma 86.7.3 in case $A$ is a G-ring. This proof is easier in that it does not depend on the somewhat delicate deformation theory argument given in the proof of Lemma 86.7.2, but of course it requires a very strong assumption on the Noetherian ring $A$.

Choose a presentation $B = A[x_1, \ldots , x_ r]^\wedge /J$. Choose generators $g_1, \ldots , g_ m \in J$. Choose generators $k_1, \ldots , k_ t$ of the module of relations between $g_1, \ldots , g_ m$, i.e., such that

\[ (A[x_1, \ldots , x_ r]^\wedge )^{\oplus t} \xrightarrow {k_1, \ldots , k_ t} (A[x_1, \ldots , x_ r]^\wedge )^{\oplus m} \xrightarrow {g_1, \ldots , g_ m} A[x_1, \ldots , x_ r]^\wedge \]

is exact in the middle. Write $k_ i = (k_{i1}, \ldots , k_{im})$ so that we have
\begin{equation} \label{restricted-equation-relations-straight-up} \sum k_{ij}g_ j = 0 \end{equation}

for $i = 1, \ldots , t$. Let $I^ c = (a_1, \ldots , a_ s)$. For each $l \in \{ 1, \ldots , s\} $ we know that multiplication by $a_ l$ on $\mathop{N\! L}\nolimits ^\wedge _{B/A}$ is zero in $D(B)$. By Lemma 86.3.4 we can find a map $\alpha _ l : \bigoplus B\text{d}x_ i \to J/J^2$ such that $\text{d} \circ \alpha _ l$ and $\alpha _ l \circ \text{d}$ are both multiplication by $a_ l$. Pick an element $f_{l, i} \in J$ whose class modulo $J^2$ is equal to $\alpha _ l(\text{d}x_ i)$. Then we have for all $l = 1, \ldots , s$ and $i = 1, \ldots , r$ that
\begin{equation} \label{restricted-equation-derivatives} \sum \nolimits _{i'} (\partial f_{l, i}/ \partial x_{i'}) \text{d}x_{i'} = a_ l \text{d}x_ i + \sum h_{l, i}^{j', i'} g_{j'} \text{d}x_{i'} \end{equation}

for some $h_{l, i}^{j', i'} \in A[x_1, \ldots , x_ r]^\wedge $. We also have for $j = 1, \ldots , m$ and $l = 1, \ldots , s$ that
\begin{equation} \label{restricted-equation-ci} a_ l g_ j = \sum h_{l, j}^ if_{l, i} + \sum h_{l, j}^{j', j''}g_{j'} g_{j''} \end{equation}

for some $h_{l, j}^ i$ and $h_{l, j}^{j', j''}$ in $A[x_1, \ldots , x_ r]^\wedge $. Of course, since $f_{l, i} \in J$ we can write for $l = 1, \ldots , s$ and $i = 1, \ldots , r$
\begin{equation} \label{restricted-equation-in-ideal} f_{l, i} = \sum h_{l, i}^ jg_ j \end{equation}

for some $h_{l, i}^ j$ in $A[x_1, \ldots , x_ r]^\wedge $.

Let $A[x_1, \ldots , x_ r]^ h$ be the henselization of the pair $(A[x_1, \ldots , x_ r], IA[x_1, \ldots , x_ r])$, see More on Algebra, Lemma 15.12.1. Since $A$ is a Noetherian G-ring, so is $A[x_1, \ldots , x_ r]$, see More on Algebra, Proposition 15.49.10. Hence we have approximation for the map $A[x_1, \ldots , x_ r]^ h \to A[x_1, \ldots , x_ r]^\wedge $ with respect to the ideal generated by $I$, see Smoothing Ring Maps, Lemma 16.14.1. Choose a large integer $M$. Choose

\[ G_ j, K_{ij}, F_{l, i}, H_{l, j}^ i, H_{l, j}^{j', j''}, H_{l, i}^ j \in A[x_1, \ldots , x_ r]^ h \]

such that analogues of equations (, (, and ( hold for these elements in $A[x_1, \ldots , x_ r]^ h$, i.e.,

\[ \sum K_{ij}G_ j = 0,\quad a_ l G_ j = \sum H_{l, j}^ iF_{l, i} + \sum H_{l, j}^{j', j''} G_{j'} G_{j''},\quad F_{l, i} = \sum H_{l, i}^ j G_ j \]

and such that we have

\[ G_ j - g_ j, K_{ij} - k_{ij}, F_{l, i} - f_{l, i}, H_{l, j}^ i - h_{l, j}^ i, H_{l, j}^{j', j''} - h_{l, j}^{j', j''}, H_{l, i}^ j - h_{l, i}^ j \in I^ M A[x_1, \ldots , x_ r]^ h \]

where we take liberty of thinking of $A[x_1, \ldots , x_ r]^ h$ as a subring of $A[x_1, \ldots , x_ r]^\wedge $. Note that we cannot guarantee that the analogue of ( holds in $A[x_1, \ldots , x_ r]^ h$, because it is not a polynomial equation. But since taking partial derivatives is $A$-linear, we do get the analogue modulo $I^ M$. More precisely, we see that
\begin{equation} \label{restricted-equation-derivatives-analogue} \sum \nolimits _{i'} (\partial F_{l, i}/ \partial x_{i'}) \text{d}x_{i'} - a_ l \text{d}x_ i - \sum h_{l, i}^{j', i'} G_{j'} \text{d}x_{i'} \in I^ MA[x_1, \ldots , x_ r]^\wedge \end{equation}

for $l = 1, \ldots , s$ and $i = 1, \ldots , r$.

With these choices, consider the ring

\[ C^ h = A[x_1, \ldots , x_ r]^ h/(G_1, \ldots , G_ r) \]

and denote $C^\wedge $ its $I$-adic completion, namely

\[ C^\wedge = A[x_1, \ldots , x_ r]^\wedge /J',\quad J' = (G_1, \ldots , G_ r)A[x_1, \ldots , x_ r]^\wedge \]

In the following paragraphs we establish the fact that $C^\wedge $ is isomorphic to $B$. Then in the final paragraph we deal with show that $C^ h$ comes from a finite type algebra over $A$ as in the statement of the lemma.

First consider the cokernel

\[ \Omega = \mathop{\mathrm{Coker}}(J'/(J')^2 \longrightarrow \bigoplus C^\wedge \text{d}x_ i) \]

This $C^\wedge $ module is generated by the images of the elements $\text{d}x_ i$. Since $F_{l, i} \in J'$ by the analogue of ( we see from ( we see that $a_ l \text{d}x_ i \in I^ M\Omega $. As $I^ c = (a_ l)$ we see that $I^ c \Omega \subset I^ M \Omega $. Since $M > c$ we conclude that $I^ c \Omega = 0$ by Algebra, Lemma 10.19.1.

Next, consider the kernel

\[ H_1 = \mathop{\mathrm{Ker}}(J'/(J')^2 \longrightarrow \bigoplus C^\wedge \text{d}x_ i) \]

By the analogue of ( we see that $a_ l J' \subset (F_{l, i}) + (J')^2$. On the other hand, the determinant $\Delta _ l$ of the matrix $(\partial F_{l, i}/ \partial x_{i'})$ satisfies $\Delta _ l = a_ l^ r \bmod I^ M C^\wedge $ by ( It follows that $a_ l^{r + 1} H_1 \subset I^ M H_1$ (some details omitted; use Algebra, Lemma 10.14.5). Now $(a_1^{r + 1}, \ldots , a_ s^{r + 1}) \supset I^{(sr + 1)c}$. Hence $I^{(sr + 1)c}H_1 \subset I^ M H_1$ and since $M > (sr + 1)c$ we conclude that $I^{(sr + 1)c}H_1 = 0$.

By Lemma 86.3.5 we conclude that multiplication by an element of $I^{2(sr + 1)c}$ on $\mathop{N\! L}\nolimits ^\wedge _{C^\wedge /A}$ is zero (note that the bound does not depend on $M$ or the choice of the approximation, as long as $M$ is large enough). Since $G_ j - g_ j$ is in the ideal generated by $I^ M$ we see that there is an isomorphism

\[ \psi _ M : C^\wedge /I^ MC^\wedge \to B/I^ MB \]

As $M$ is large enough we can use Lemma 86.7.1 with $d = d(I \subset A \to B)$, with $C^\wedge $ playing the role of $B$, with $2(rs + 1)c$ instead of $c$, to find a morphism

\[ \psi : C^\wedge \longrightarrow B \]

which agrees with $\psi _ M$ modulo $I^{q - 2(rs + 1)c}$ where $q$ is the quotient of $M$ by the number of generators of $I$. We claim $\psi $ is an isomorphism. Since $C^\wedge $ and $B$ are $I$-adically complete the map $\psi $ is surjective because it is surjective modulo $I$ (see Algebra, Lemma 10.95.1). On the other hand, as $M$ is large enough we see that

\[ \text{Gr}_ I(C^\wedge ) \cong \text{Gr}_ I(B) \]

as graded $\text{Gr}_ I(A[x_1, \ldots , x_ r]^\wedge )$-modules by More on Algebra, Lemma 15.4.2. Since $\psi $ is compatible with this isomorphism as it agrees with $\psi _ M$ modulo $I$, this means that $\text{Gr}_ I(\psi )$ is an isomorphism. As $C^\wedge $ and $B$ are $I$-adically complete, it follows that $\psi $ is an isomorphism.

This paragraph serves to deal with the issue that $C^ h$ is not of finite type over $A$. Namely, the ring $A[x_1, \ldots , x_ r]^ h$ is a filtered colimit of ├ętale $A[x_1, \ldots , x_ r]$ algebras $A'$ such that $A/I[x_1, \ldots , x_ r] \to A'/IA'$ is an isomorphism (see proof of More on Algebra, Lemma 15.12.1). Pick an $A'$ such that $G_1, \ldots , G_ m$ are the images of $G'_1, \ldots , G'_ m \in A'$. Setting $C = A'/(G'_1, \ldots , G'_ m)$ we get the finite type algebra we were looking for. $\square$

The following lemma isn't true in general if $A$ is not a G-ring but just Noetherian. Namely, if $(A, \mathfrak m)$ is local and $I = \mathfrak m$, then the lemma is equivalent to Artin approximation for $A^ h$ (as in Smoothing Ring Maps, Theorem 16.13.1) which does not hold for every Noetherian local ring.

Lemma 86.8.1. Let $A$ be a Noetherian G-ring. Let $I \subset A$ be an ideal. Let $B, C$ be finite type $A$-algebras. For any $A$-algebra map $\varphi : B^\wedge \to C^\wedge $ of $I$-adic completions and any $N \geq 1$ there exist

  1. an ├ętale ring map $C \to C'$ which induces an isomorphism $C/IC \to C'/IC'$,

  2. an $A$-algebra map $\varphi : B \to C'$

such that $\varphi $ and $\psi $ agree modulo $I^ N$ into $C^\wedge = (C')^\wedge $.

Proof. The statement of the lemma makes sense as $C \to C'$ is flat (Algebra, Lemma 10.142.3) hence induces an isomorphism $C/I^ nC \to C'/I^ nC'$ for all $n$ (More on Algebra, Lemma 15.83.2) and hence an isomorphism on completions. Let $C^ h$ be the henselization of the pair $(C, IC)$, see More on Algebra, Lemma 15.12.1. Then $C^ h$ is the filtered colimit of the algebras $C'$ and the maps $C \to C' \to C^ h$ induce isomorphism on completions (More on Algebra, Lemma 15.12.4). Thus it suffices to prove there exists an $A$-algebra map $B \to C^ h$ which is congruent to $\psi $ modulo $I^ N$. Write $B = A[x_1, \ldots , x_ n]/(f_1, \ldots , f_ m)$. The ring map $\psi $ corresponds to elements $\hat c_1, \ldots , \hat c_ n \in C^\wedge $ with $f_ j(\hat c_1, \ldots , \hat c_ n) = 0$ for $j = 1, \ldots , m$. Namely, as $A$ is a Noetherian G-ring, so is $C$, see More on Algebra, Proposition 15.49.10. Thus Smoothing Ring Maps, Lemma 16.14.1 applies to give elements $c_1, \ldots , c_ n \in C^ h$ such that $f_ j(c_1, \ldots , c_ n) = 0$ for $j = 1, \ldots , m$ and such that $\hat c_ i - c_ i \in I^ NC^ h$. This determines the map $B \to C^ h$ as desired. $\square$

Comments (0)

Post a comment

Your email address will not be published. Required fields are marked.

In your comment you can use Markdown and LaTeX style mathematics (enclose it like $\pi$). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).

Unfortunately JavaScript is disabled in your browser, so the comment preview function will not work.

All contributions are licensed under the GNU Free Documentation License.

In order to prevent bots from posting comments, we would like you to prove that you are human. You can do this by filling in the name of the current tag in the following input field. As a reminder, this is tag 0ALU. Beware of the difference between the letter 'O' and the digit '0'.